Gejala dan Intensitas Serangan Serangga Fitofagus pada Sagu [The Symptoms and Intensity Attacks of Phytophagous Insects on Sago] - Rein Estefanus Senewe; Hermanu Triwidodo; Nfn Pudjianto; Aunu Rauf; Marietje Pesireron (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
The growth and development of sago palm naturally interact with the organism such as insects. The symptoms of damage to the plant canopy sago indicate a relationship between insects and plants. This study aims to identify phytophagous insects, symptoms of damage and attack rates on sago plants. The study was conducted in the village of Rutong and Tulehu in Maluku, starting in June until September 2016. There are 10 plants/sago clump in each observations in each location determined by purposive sampling. Each sago clump in the growth phase (seedlings, tillers, a trunk stage, and stems / trees), observed symptoms of damage to leaflets and leaf midribs. The results showed four symptoms of attack on the sago canopy with an average intensity of mild attacks. The highest incidence of attack was 37.5% in the phase of a trunk stage with the symptoms of cutout attacks on the leaves. Then seven species phytophag insects were obtained which were associated with sago canopy. Each of the insect imago phases leads to leaf damage with distinctive features, which can potentially cause severe damage to the canopy of the sago plant.ABSTRAKPertumbuhan dan perkembangan tanaman sagu secara alami berinteraksi dengan organisme diantaranya serangga. Gejala kerusakan tajuk tanaman sagu menunjukkan adanya hubungan antara serangga dan tanaman. Tujuan penelitian adalah untuk mengidentifikasi serangga fitofag, gejala kerusakan dan tingkat serangan pada tanaman sagu. Penelitian dilakukan pada areal sagu di Desa Rutong dan Tulehu Provinsi Maluku, dimulai bulan Juni – September 2016. Tersedia 10 tanaman/rumpun sagu ditiap lokasi pengamatan yang ditentukan secara purposive sampling. Setiap rumpun sagu pada fase pertumbuhan (semai, anakan, sapihan, dan batang/pohon), diamati gejala kerusakan anak daun dan pelepah daun. Hasil penelitian menunjukkan empat gejala serangan pada tajuk tanaman sagu dengan rata-rata intensitas serangan ringan. Insidensi serangan tertinggi (37.5%) pada fase sapihan dengan gejala serangan bentuk guntingan pada daun. Selanjutnya diperoleh tujuh jenis serangga fitofagus yang berasosiasi dengan tajuk tanaman sagu. Masing-masing fase imago serangga menimbulkan kerusakan daun dengan ciri khas berbeda, sehingga dapat berpeluang menimbulkan kerusakan berat pada tajuk tanaman sagu.